Optimization of Kamsel Unit Performance Through Dikmas Lantas Safety Riding to Prevent Traffic Accident - Redyatama, Ardhinia (Indonesian Journal of Police Studies, 2024)
This research is motivated by the high number of traffic accidents that occur in Brebes Regency. To reduce the number of traffic accidents, it is necessary to carry out Traffic Community Education (Dikmas Lalu) carried out by the Kamsel Unit. The purpose of implementing Dikmas Lalu is to increase knowledge and community support to create security, safety, order and smooth traffic. One of the programs contained in Dikmas Lalu is safety riding. Safety riding isa form of driving behavior in which the driver has the awareness to demonstrate safe and secure driving ethics for both himself and others. In discussing this research, the authors use management theory (POAC and 6M), SWOT theory, the concept of optimization, the concept of DikmasThen, and the concept of safety riding. This study uses a qualitative approach with a research focus on optimizing the performance of the Kamsel Unit through DikmasThensafety riding to prevent traffic accidents at Polres Brebes. Sources of data come from members and officers of the Kamsel Unit, author’s observations, and document review. The validity of the data was proven by data triangulation and analyzed by data reduction techniques, data presentation, and drawing conclusions. The results of research conducted by the authors found that there were still deficiencies in the elementsman, machine, method, and market. Therefore, the author provides a solution to the problem in the form of a BKO request from another unit, utilizes information technology using a method that invites the sympathy of participants, and expands the goals of Dikmas Then. The conclusion from this research is that in the implementation of Dikmas. Then, the organizing and implementation functions are not optimal. In organizational resources, elements man and method also requires optimization.